A method to assess the suffusion susceptibility of low permeability core soils in compacted dams based on construction data. Issue 5 (4th May 2019) - Zhang, Lingran; Gelet, Rachel; Marot, Didier; Smith, Marc; Konrad, Jean-Marie
Abstract: Suffusion, as one of the main internal erosion processes in earth structures and their foundations, may increase their failure risks. The paper aims at presenting a general method to assess the suffusion susceptibility of core soil samples belonging to zoned hydraulic embankment dams. On one hand, the suffusion susceptibility of the soil samples is evaluated by an erosion resistance index. Thanks to existing statistical analyses, the erosion resistance index is estimated from several soil parameters that can be easily measured in situ or in laboratory during the construction of a dam. On the other hand, the saturated hydraulic conductivity of the soil samples is evaluated based on the amount of fines content and on available construction data. Moreover, the power dissipated by the flow is inferred based on the saturated hydraulic conductivity and simplified fluid boundary conditions. The combined consideration of the erosion-resistant index and of the power dissipated by the flow permits to identify zones characterised with a relatively larger suffusion potential (lower erosion resistance index and larger power than their respective average). Throughout, the method is applied to a particular zoned dam with a till core, from Northern Quebec, as a proof of concept.